CONTENT ANALYSIS IS A NECESSARY SOURCE STUDY PROCEDURE FOR MATERIALS OF THE CHANCELLERY OF THE TURKESTAN GOVERNORATE GENERAL - Ergashev Bakhtiyar Ergashevich (Western European Studies, 2024)
The history of Uzbekistan, free from various theoretical isms, is increasingly included in the world system of using advanced achievements in the field of science. Information on the content analysis of the study of the original materials of the court of the Turkestan General Governorate is presented.
Keywords: Turkestan; governorship; content analysis; historical reality